The Relationship between PROLANIS Exercise Routine and Quality of Life in Hypertensive Patients in Puskesmas Oesapa, Kupang City - Wijoyo, Adinda Savely Kend Amara; Koamesah, Sangguana Marthen Jacobus; Wungouw, Herman Pieter Louis; Handoyo, Nicholas Edwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hypertension is one of the leading causes of premature death worldwide, including in Indonesia. East Nusa Tenggara Province (NTT) has a high prevalence of hypertension, yet awareness and treatment rates remain low. In Kupang City, Puskesmas Oesapa reports the highest number of hypertension cases. PROLANIS exercise, a non-pharmacological intervention, is considered effective in improving patients quality of life. This study aims to determine the relationship between PROLANIS exercise routine and quality of life of hypertensive patients in the working area of Puskesmas Oesapa. Objective: To investigate the association between the routine participation in PROLANIS exercise and the quality of life of hypertensive patients in working area of Puskesmas Oesapa. Methods: This study used an analytical observational design with a cross-sectional approach. Data were collected through medical records and questionnaires, including medication adherence and the WHOQOL-BREF instrument. Sampling was conducted using total sampling technique and analyzed using Spearman correlation test. Results: The results showed a significant relationship between PROLANIS exercise routine and the quality of life of hypertensive patients, with a p-value of 0.041 (p < 0.05). Conclusion: A higher frequency of PROLANIS exercise is associated with better quality of life in hypertensive patients. Therefore, promoting regular participation in PROLANIS exercise should be considered as a strategy to improve the quality of life in this population.